Agents of change: Empowering rural youth as entrepreneurs - Babu, Suresh Chandra (Syngenta Foundation, 2022)
The challenge of the ‘youth bulge’ The global youth population is growing. Youth account for the largest share of the population in many countries. This phenomenon is often referred to as the ‘youth bulge’. It puts enormous pressure on governments to provide adequate education and employment opportunities. Global youth unemployment was estimated at 15.6 percent in 2021, significantly higher than for adults. Most youth in Africa and Asia still live in the countryside. In 2019, young people in rural areas around the globe were more likely to be in the labor force than their urban counterparts. The rural-urban gap in youth labor force participation is particularly high in Africa and low-income countries.